Factors Influencing The Implementation Of Waste Management Policies By The Yogyakarta City Environmental Service - Cut Laila Karmila; Diah Ayu Kuswardani (Sean Institute, 2024)
Waste is a problem that cannot be ignored by the government, because waste arises as a result of human activity. The more human activity, the more waste produced. The implementation of waste management certainly varies in each region of Indonesia. This research was conducted at the Yogyakarta City Environmental Service using a qualitative descriptive method. The theory used is the theory of policy implementation according to Edward III, namely communication, resources, disposition and bureaucratic structure. The data collection techniques used are interviews, observation and documentation. The technical data analysis carried out is data reduction, data presentation, drawing conclusions and data verification. The research results show that the implementation of waste management policies by the Yogyakarta City Environmental Service has not been carried out optimally, characterized by a lack of communication and community support, a lack of staff and facilities for waste management. The supporting factor is having clear technical instructions in implementing waste management policies. Staff who are experts in their fields, organizational structure that complies with regulations. The inhibiting factors are the lack of awareness and support from the community, funds, number of workers, facilities and infrastructure. Efforts made include outreach regarding waste management, proposing to increase the number of waste workers, requesting assistance for facilities and infrastructure, budgeting funds according to the waste management needs of the City of Yogyakarta. Researchers suggest that the Yogyakarta City Environmental Service should carry out comprehensive outreach to increase public awareness, create more mature strategies in requesting assistance for infrastructure, allocate funds optimally to meet waste management needs and improve monitoring of waste management conditions.